From Mawlid Tradition to Affective Pedagogy: A Framework for Elementary Character Education - Fira Ardillah (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2026)
This study aims to conceptualize the Mawlid tradition of Prophet Muhammad SAW as a foundation for affective learning in elementary education. Character education remains urgent amid rapid social, technological, and cultural changes that influence children’s moral awareness, empathy, and spiritual values. However, existing moral education practices often emphasize cognitive understanding and ritual participation rather than systematic affective internalization. This study employed a qualitative library research design by reviewing scholarly publications, books, and relevant studies published between 2021 and 2025. Data were analyzed through descriptive-analytical and thematic procedures involving data extraction, classification of values, interpretation, and conceptual synthesis. The findings show, first, that the Mawlid tradition contains core affective values, including love for the Prophet, empathy, responsibility, honesty, and respect for others. Second, these values can be internalized through collaborative, reflective, creative, social, and curriculum-integrated activities. Third, Mawlid-based affective learning supports moral knowing, moral feeling, moral action, and socially embedded character formation. This study contributes a culturally grounded framework for Islamic elementary character education. Future research should empirically test its effectiveness in classroom practice.